What the waves know - Valentine, Tamara (William Morrow, an imprint of HarperCollins Publishers, 2016)
"On the sharp crags of tiny Tillings Island lies the secret of Izabella Rae Haywood's sixth birthday. That night, her father vanished, taking her voice, and the truth of what really happened along with him"--